Analisis Kinerja Pegawai pada Direktorat Sumber Daya, Ditjen Dikti Kemendikbud - Santi Sayanti Agustina; Tatan Sukwika (Journal of Applied Management Research, 2021)
[Employee Performance Analysis in Directorate of Resources, Directorate General of Higher Education, Ministry of Education and Culture]. The performance indicators of the Directorate of Resources program in 2019 have not been maximized, only 77.60% has been achieved. For this reason, this study was conducted, which aims to determine the influence of internal employee factors, leadership, work team, work system and work environment on employee performance in the Directorate of Resources, so that we can get a picture and find out how much the relationship and influence on each variable to improve and improve the performance of employees in the Directorate of Resources. The analysis of this research uses a linkert scale and a rating scale, and hypothesis testing is carried out by analyzing Partial Least Squares Structural Equation Modeling (PLS-SEM) with the SmartPLS 3 application. The result of the research was obtained, employee internal factors, leadership, work team, work system and work environment. has an influence on employee performance. And employee internal factors that most dominantly affect employee performance in the Directorate of Resources. Based on this, efforts are needed for further research by exploring and developing other variables that can affect performance. Likewise, the object of research can be carried out on the same object or on different objects. Keywords: Performance, Internal factors, Leadership, Work team, and Work environment